The Contextual Semantic Realizations Of The Lexial Units “Hesitate, Waver, Vacillate, and Falter” and “Hesitation, Hesitancy” - Alla, Gnatiuk (Lesya Ukrainka Eastern European National University, 2017)
This article is dedicated to the research of synonymous groups for the designation of doubt “Hesitate, Waver, Vacillate, Falter” and “Hesitation, Hesitancy” in contemporary English-language fictional discourse. Doubt is defined as an epistemic state in the cognitive world of individuals which provides motivation to undertake a further quest for information. The purpose of this work is to investigate how the set of semes identified in each component of the synonymous group is presented in the context of modern English fictional discourse. This research is directed towards verifying whether the use of all the components of the given synonymous groups is of equal importance in modern language discourse, as well as checking whether all the semes of “Hesitate, Waver, Vacillate, Falter” and “Hesitation, Hesitancy” are used correctly, based on the results of the componential analysis. The results of the research make it possible to form conclusions regarding the homogeneity or heterogeneity of contextual sematic representations in discourse, dependent upon the number of constituents which make up the synonymous group. Стаття присвячена дослідженню синонімічних рядів на позначення сумніву “Hesitate, Waver, Vacillate, Falter” та “Hesitation, Hesitancy” у сучасному художньому англомовному дискурсі. Сумнів дефініціюється як епістемічний стан, що має місце у когнітивному світі людини та є рушійною силою до пошуку нової інформації. Дослідження має на меті виявити, яким чином набір сем, виділений у складі кожного компонента синонімічного ряду, представлений у контексті сучасного художнього англомовного дискурсу. Науковий пошук спрямовано для розпізнавання тенденції представлення компонентів синонімічного ряду у сучасному дискурсі, переважання чи відсутності деяких його складників, а також із метою з’ясування подібностей та відмінностей між набором сем, виявлених у результаті компонентного аналізу та фактичним набором, представленим у дискурсі. Отримані результати допомагають зробити висновок про гомогенність чи гетерогенність представлення семного набору у дискурсі.
Keywords: doubt; epistemic state; fictional discourse; synonymous group; seme; contextual realization; сумнів; епістемічний стан; художній дискурс; синонімічний ряд; сема; контекстуальна реалізація